The Relationship Between Credit Supply, Capital Structure and Firm Performance of Listed Real Estate Firms: Evidence from an Emerging Country - Dinh Long Tran; Duy Tinh Pham; Quang Khai Nguyen (SAGE Open)
This study investigates the relationship between capital structure and firm performance, concentrating on the moderating influence of monetary policy by means of bank credit. By using a sample of 49 real estate firms listed on the Ho Chi Minh City Stock Exchange between 2007 and 2021 and applied some econometric models such as ordinary least squares, fixed-effects, random effects estimation, and two-step system GMM, this research pioneers the concept of a minimum debt threshold or lower-bound debt threshold, addressing theoretical and empirical gaps in the evaluation of the effects of maintaining debt levels below this threshold, in contrast to traditional studies that primarily emphasize the optimal debt level or maximum debt threshold. Moreover, the study highlights the semi-moderating impact of bank credit on the threshold, emphasizing the important interaction between monetary policy and capital structure decisions. Specifically, this study finds that debt financing below the minimum threshold has a negative impact on performance, encouraging firms to seek alternative capital solutions or increase leverage above the minimum threshold, which is defined for each industry in accordance with the context of individual economies. The research offers significant insights for companies in capital budgeting and adjusting to variations in credit policies, particularly within Vietnamese real estate sector, which is highly dependent on debt financing and sensitive to monetary changes. JEL Classification: E51, E52, G32.